PD-009 A Phase 2B, Multicenter, Randomized, Placebo-Controlled Dose-Ranging Trial of Peficitinib, an Oral JAK Inhibitor, in Patients with Moderately-Severely Active UC. (February 2017) - Sands, Bruce; Sandborn, William; Feagan, Brian; Lichtenstein, Gary; Zhang, Hongyan; Szapary, Philippe; Panes, Julian; Vermeire, Severine; Christopher, O. O''Brien; Dewey, Julia; Yang, Zijiang; Johanns, Jewel; et al.
Abstract : Background: Janus kinases (JAK) are intracellular signaling molecules central to immune responses in IBD. We studied dose-response and safety of peficitinib, an oral JAK inhibitor, in patients with moderate-severe UC. Methods: Eligible patients had moderate-severe UC (Mayo score of 6–12, including a centrally read endoscopy subscore ≥2) and an inadequate response to, or failure to tolerate corticosteroids, immunosuppressives, or TNF antagonists. Patients were randomized at wk 0 to PBO (n = 43), peficitinib 25 mg qd, 75 mg qd, 150 mg qd, or 75 mg bid (n = 44 per group) through wk 8. Primary endpoint was change from baseline Mayo score at wk 8; Multiple Comparison Procedures method was used to analyze the dose response for qd regimens. Secondary endpoints (using central endoscopic subscore) included clinical response and remission and mucosal healing at wk 8. Safety was evaluated through wk 8. Results: Two hundred nineteen patients were randomized. Baseline characteristics and concomitant medications were generally similar amongst treatment groups. The primary endpoint of dose response for qd regimens of peficitinib was not met (adjusted P -values for candidate dose response curves were > 0.05). However, change from baseline in Mayo score at wk 8 was numerically higher for peficitinib doses ≥ 75 mg qd versus PBO (−2.3 [25 mg qd], −3.1 [75 mg qd], −2.8 [150 mg qd], versus −2.4 [PBO]); none reached statistical significance. Trends for efficacy were observed for peficitinib doses ≥75 mg qd based on the proportion of patients with clinical response (34.1% [25 mg qd], 54.5% [75 mg qd], 54.5% [150 mg qd], 54.5% [75 mg bid] versus 39.5% [PBO]), clinical remission (15.9% [25 mg qd], 15.9% [75 mg qd], 27.3% [150 mg qd], 15.9% [75 mg bid] versus 7.0% [PBO]) and mucosal healing (20.5% [25 mg qd], 29.5% [75 mg qd], 45.5% [150 mg qd], 36.4% [75 mg bid], versus 18.6% [PBO]). Changes in CRP and fecal markers did not yield consistent evidence of an effect. AE rates were higher across peficitinib groups versus PBO through wk 8 (45.5% [combined] versus 34.9% [PBO]) mainly occurring in ≥ 75 mg qd dose groups. Most common AEs were UC (5.7% [combined] versus 9.3% [PBO]), CPK increase (4.0% [combined] versus 0.0% [PBO]), and anemia (4.0% [combined] versus 4.7% [PBO]). Rates of discontinuation due to an AE were similar between combined peficitinib groups and PBO (8.0% and 7.0%, respectively). SAEs were uncommon (3.4% [combined] versus 4.7% [PBO]). One basal cell carcinoma (25 mg qd before wk 8) and one pancreatic cancer (PBO; fatal, after wk 8) occurred. Incidences of infection were similar (12.5% [combined] versus 14.0% [PBO]). Serious infections were rare; no tuberculosis or opportunistic infections, including herpes zoster, were reported. There were modest increases in fasting lipids, including TC and HDL, for doses of peficitinib ≥ 75 mg qd. Modest, transient elevations in CPK were observed with 150 mg qd and 75 mg bid peficitinib. Conclusions: Peficitinib did not demonstrate a dose response based on mean change from baseline Mayo score at wk 8 in patients with moderate-severe UC. Trends for greater proportions of patients achieving clinical response, clinical remission, and mucosal healing were observed at doses ≥75 mg qd. The safety profile of peficitinib through wk 8 was generally consistent with the known safety profile of JAK inhibitors.